The emergence of multinational enterprises: Simulation results - Jörn Kleinert (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
In the last decades, foreign direct investment (FDI) has increased strongly among industrialised countries. U.S. companies were the first to set up foreign affiliates followed later by companies from smaller industrialised countries. This paper develops a general equilibrium model of bidirectional intra-industry FDI between industrialised countries, in which this specific time pattern emerges. In contrast to the existing literature on FDI, this paper shows that falling transport costs first lead to increased FDI activities and only later to decreased FDI. Additionally, FDI is more likely to occur in industries with differentiated products, higher scale economies on company relative to plant level, smaller inputs of intermediate goods and more differentiated intermediate goods.
Keywords: F12; F21; F23; 330; Direktinvestition; Multinationales Unternehmen; Industriegüteraußenhandel; Neue Außenhandelstheorie; Allgemeines Gleichgewicht; Transportkosten; Theorie